Switched-Capacitor Nine-Level Inverter - Ngo, Bac Bien; Nguyen, Minh Khai; Ngo, Van Thuyen (Old Journal, 2017)
This paper proposes a new configuration of the switched-capacitor multilevel inverter (SCMI). The proposed switched-capacitor nine-level inverter configuration based on switching the capacitors in series and in parallel through the semiconducting switches. The proposed topology does not use more power supplies to raise the output voltage level or the transformers to boost output voltage, moreover the proposed inverter of components are used less than the traditional inverter configuration, thereby reducing the cost and size of the system. To verify the circuit operation, PSIM simulation is performed for 9-level configuration. The experimental results are also shown with 9-level inverter configuration.